1984
DOI: 10.1128/iai.46.2.585-589.1984
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of in vitro human lymphocyte response by the pneumococcal toxin pneumolysin

Abstract: The effects of pneumolysin, a sulfhydryl-activated cytolytic toxin produced by Streptococcus pneumoniae, on the in vitro human lymphocyte response was examined. The toxin, at concentrations of one to five hemolytic units per ml, caused marked inhibition of the response of lymphocytes to concanavalin A, phytohemagglutinin, pokeweed mitogen, and protein A. The response was assessed by measuring both [3HJthymidine incorporation and the ability of lymphocytes to produce immunoglobulins and lymphokine activity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…According to our results, the vaccination with plain PS is followed by a situation in which the lymphocyte proliferative responses to the protein antigens tested declined by day 14. It is difficult to know whether this is related to the pathogenesis of pneumococcal infections, as the pneumococcal protein antigen can inhibit mitogenic proliferative responses and antibody synthesis [27]. On the other hand, we have observed a comparable immunosuppressive influence of ongoing bacterial [28] infections on in vitro proliferative responses to that of nonrelated protein antigens and have regarded it as being as a result of active ongoing immunological reactions against the microbe in question.…”
Section: Discussionmentioning
confidence: 91%
“…According to our results, the vaccination with plain PS is followed by a situation in which the lymphocyte proliferative responses to the protein antigens tested declined by day 14. It is difficult to know whether this is related to the pathogenesis of pneumococcal infections, as the pneumococcal protein antigen can inhibit mitogenic proliferative responses and antibody synthesis [27]. On the other hand, we have observed a comparable immunosuppressive influence of ongoing bacterial [28] infections on in vitro proliferative responses to that of nonrelated protein antigens and have regarded it as being as a result of active ongoing immunological reactions against the microbe in question.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, there is an increasing body of evidence that pneumolysin, a thiol-activated toxin produced by virtually all clinical isolates of S. pneumoniae, is directly involved in pathogenesis. In vitro studies showed that very low doses of purified pneumolysin inhibit the bactericidal properties of human polymorphonuclear leukocytes and macrophages (16,18) as well as the proliferative response of human lymphocytes to mitogens (7). Higher toxin doses also cause activation of the classical complement pathway and depletion of serum opsonic activity (20).…”
mentioning
confidence: 99%
“…For this reason, we have been studying the role of pneumococcal protein toxins, in particular pneumolysin and neuraminidase, in pneumococcal pathogenesis. We have shown that pneumolysin has a variety of detrimental effects in vitro on components of the human immune system (7,23,25,27). Immunization of mice with purified pneumolysin also confers partial protection against challenge with virulent pneumococci (26).…”
mentioning
confidence: 99%